Les albums de Jean de Brunhoff : usages de la couleur - Isabelle Nières-Chevrel (Strenae)
Starting with the (all too exclusively) famous suit of a pleasant green color, this study analyses the two main purposes of the colors Jean de Brunhoff used in his five picture books produced entirely in his own hand. The original purpose of color, that of individualization, allows a reader to identify the protagonists (for how else could we distinguish between so many gray elephants?), while the latter purpose involves page layout and using the double page for narrative space. This analysis shows how clothing, far from being reduced to an anthropomorphic marker, is, for Babar, an ontological and social stake, and that his wardrobe obeys in part social codes, and in part chromatic organizational choices regarding the opposite page and the large double pages. Color thus often opposes or links narrative sequences, marks the passage of time, and dramatizes the turning of the page, conveying a subjective point of view and rendering it lyrical.